SPIN MODEL OF FULL SUMMATOR ON PERES GATES - Deibuk, Vitaliy; Yuriychuk, Ivan; Yuriychuk, Roman (International Journal of Computing, 2014)
Four-spin model of single-digit summator for solid state nuclear magnetic resonance (NMR) quantum computer is proposed. Correctness of summator’s operation is analyzed in dependence of system parameters. It is found that the summator on Peres gates works correctly in time of four π-pulses on pure numerical and superposition states. Optimal values for exchange in teractions and maximum distance between q- bits necessary for correct summator’s operation are obtained from the analysis of fidelity function.